Peran Kepemimpinan Transformasional Kepala Sekolah dalam Implementasi Supervisi Akademik Berbasis Kolaborasi untuk Optimasi Kinerja Mengajar Guru - Kusumawati, Erna (Jayapangus Press, 2023)
This study investigates the role of principals' transformational leadership in optimizing teacher teaching performance through collaborative academic supervision. The background of this study is the urgency of improving the quality of education that is highly dependent on the effectiveness of teacher teaching, where the role of the principal as a leader is very important in facilitating teacher professional development. The purpose of this study is to analyze the implementation of principals' transformational leadership, the characteristics of collaborative supervision carried out, and its impact on improving teacher teaching performance. This study uses a qualitative multi-site case study method, allowing for in-depth exploration of the phenomenon in several locations. Data were collected through interviews, observations, and documentation, then analyzed and validated through data triangulation. The results of the study indicate that the principal's transformational leadership effectively fosters equal dialogue and the development of joint follow-up plans between the principal and teachers. The implementation of this collaborative academic supervision has a significant impact on improving teacher performance including aspects of better lesson planning, innovative teaching strategies, effective classroom management, deep self-reflection skills, and increased teacher self-efficacy. The conclusion of the study explains that the principal's transformational leadership is a key factor in creating a conducive environment for teacher professional development through collaborative supervision, which ultimately contributes to improving the quality of teaching holistically. This study makes an important contribution to the development of an empowering supervision model, emphasizing the role of the principal as a change agent who empowers teachers to reach their maximum potential.